دراسة تشخيصية ومسحية للمصابين بمرض نزف الدم الوراثي(الهيموفيليا) في محافظة القادسية - محمد حسون الاء; ثامر مهدي وجدان; عبد جواد وداد (University of Thi-Qar Journal of Science, 2011)
This study aims to diagnosis some of the sickness cases by (Haemophilia) on some patients in three different healthy centers in al-Dewanya city . For such purpose , fifty cases of sickness by such disease are collected and laboratory test on them are made to identify them clearly . The results explain that 84% of those patients who have (haemophilia) of the type A, which results from the loss of the factor 144, and roushly %12 from them who have haemophilia of the type of B which results from the loss of the factor XI what is concerned with the haemophilia of the type of C which results from the loss of factor 144 and the Haemophilia which results of the deficit of well brand element . Their percentage are %2 . Also the results of the rest of (H.I.V.) that approximately %10 from those patients who afflicted by this disease and about %20 from them who afflict by C virus hepatitis as the results of (H.C.V.). The rest percentage is not suffered from any secondary in addition to this the results explain that spread of this disease among male is more than female.